The Home Garden System as a Source of Cultivated Plant Species Diversity and Their Developmental Uses: A Case Study in Lubang Buaya Area of East Jakarta - Kristiyanto, Kristiyanto; Hesti, Widia (Media Konservasi, 2023)
Optimizing a home garden is one way to create tenacity, which can be cultivated for plant diversity and is used in daily life as part of food or energy security, especially in urban areas. For example, in Jakarta, chiefly in the Lubang Buaya areas, at least October 2020 to November 2020 are needed to collect data in the field on the methods used to inventory, identify, and analyze plant species diversity in cultivated and used home garden systems. Hence, direct observation and in-depth individual interview methods are steps in data collection as well as in the field, where at least 10 families will become respondents in this research. The results of this research have identified some of the plant species in all of the dwellings’ home gardens—at least 50 plant species from 144 of the 10 dwellings' home gardens—and their use by local people in their daily lives. For example, which plant species (22.6%), plant species of spice species (8.4%), plant species of ornamental species (2.6%), and plant species of fruit species (14.3%) were used as medicinals by local people at least 32.1% more than the other plant species? The use of home gardens to meet the demands of a family currently has many needs. Because of the role and contribution of home gardens, which are advantageous in economic, social, and ecological aspects, they are also part of the goals of social resilience systems.